Penerapan Active Cycle of Breathing Techniques (ACBT) untuk Mengatasi Bersihan Jalan Napas pada Pasien PPOK di Instalasi Gawat Darurat - Ilham Virgo Firdaus; Dheni Koerniawan; Vincencius Surani (Jurnal Anestesi, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease characterized by persistent airflow limitation and excessive mucus production, often leading to ineffective airway clearance, a common problem for patients presenting to the Emergency Department (ED). The Active Cycle of Breathing Techniques (ACBT) is a non-pharmacological intervention designed to improve mucus clearance and breathing patterns. This scientific paper aims to describe the application of ACBT in improving airway clearance in COPD patients. The method used was a qualitative case study with a nursing care approach involving three COPD patients with ineffective airway clearance at the Emergency Department of Charitas Hospital Palembang from January to February 2026. The intervention consisted of applying the ACBT cycle, which includes breathing control, thoracic expansion exercises, and the forced expiration technique (huffing), combined with effective coughing. Airway clearance was assessed before and after the intervention. The results showed that the application of ACBT led to significant improvements in all three patients, marked by enhanced cough effectiveness, reduced sputum production, decreased dyspnea, a more stable respiratory rate, and diminished adventitious breath sounds. This evidence-based practice is expected to provide valuable information on the use of ACBT as an independent nursing intervention for managing ineffective airway clearance in COPD patients in the acute care setting.